Digital Marketing Assistance and Local Product Innovation: Development of the Village Micro Business Sector in Ponorogo - Setiawan, Suhada; Retnowati, May Shinta; Uluum, Muhammad Miftachul; Ghufron, Isa Lazuardi (Amirul Bangun Bangsa, 2025)
Competition in the snack industry has its own attraction for manufacturers which has a big impact on consumers in choosing products. This level of competition does not only occur among large companies, but also in the small and medium enterprises (MSMEs) sector, as for effective ways to conduct business competition that attracts the attention of consumers by utilizing digital marketing. This strategy is very relevant to be applied in the era of the industrial revolution 5.0 The implementation of this service activity aims to explore the application of digital media as an appropriate marketing tool in business competition that is able to strengthen the competitiveness of culinary MSMEs in villages in Ponorogo. This community service using the ABCD (Asset Based Community Development) method to carry out community service based on strength and potential methodthat uses a thematic approach consists of three primary stages, namely the socialization, mentoring, and evaluation monitoring stages. The results of this activity show that the use of digital marketing as a promotional tool by one of the local MSMEs, Anna Snack in Nampan Village, is still limited. However, with the implementation of digital marketing strategies through platforms such as e-commerce and social media, there has been a significant increase in the understanding and skills of MSME actors. This activity has proven to have a positive impact in increasing marketing targets and strengthening the image of snack MSMEs on social media, which contributes to increased sales. The use of digital media as part of the MSME marketing strategy can continue to be developed to have a positive impact on global economic growth